Archaeological perspectives in information science. Issue 1 (24th October 2017) - Huvila, Isto; Olsson, Michael; Faniel, Ixchel M.; Dalbello, Marija; Dallas, Costis
ABSTRACT: Archaeology is a domain that has intersections with information science and technology research both as an empirical domain of investigation and as a perspective to inquire into how people interact with information. The aim of this panel is to highlight this interdisciplinary nexus of diverse engagements and to explicate how archaeology has informed and could inform information science research and practice in the future, and how empirical information science research on archaeological practices has enhanced our understanding of both archaeological work and human information behavior and practices in general.